A ruszin és az ukrán népi folklór tragédiái magyar nyelven - Cs. Jónás Erzsébet (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2021)
A ruszinok Ukrajnában a magyar, szlovák, lengyel határvidék mentén, a Kárpátok hegyvidékén élnek. A ruszin és ukrán balladákat négy témakör köré csoportosíthatjuk: történeti tárgyú balladák, betyártörténetek, tragikus szerelemről szóló balladák, családi szerencsétlenségeket és tragédiákat hordozó balladai történetek. Vári Fábián László kárpátaljai magyar költő, műfordító, folklorista, aki a kárpátaljai ruszin és ukrán balladákkal egyetemistaként kezdett ismerkedni, később sokat lefordított közülük magyar nyelvre. A párhuzamok és különbségek felismerése vonzóvá teszik ezeket a „dalban elmondott tragédiákat” a mai olvasók számára is. A „hermeneutikai ív” kapcsolja össze a szöveget és az olvasót. Dolgozatunk a ruszin és ukrán népballadák kulturális hátterével, a hasonlóságok és különbségek rendszerezésével foglalkozik. Rámutat a fordításokban levő stilisztikai értékekre is.

Abstract. Rusyns live in Ukraine, near the Hungarian, Slovakian and Polish borders in the northeastern regions of the Carpathian Mountains. Rusyn and Ukrainian ballads have four big thematic groups: historical ballads, legends of outlaws, tragic love stories and the stories of family calamities or tragedies. Laszlo Vari Fabian, a poet, translator and folklorist from Zakarpattia Oblast started learning more about these folk ballads during his university studies and later he translated several of them into Hungarian. The recognition of the similarities and differences makes these ‘folk song tragedies’ very attractive for the readers today, too. The ‘hermeneutic circle’ connects the reader and the story. In this paper we highlight the cultural origin of Rusyn and Ukrainian folk ballads and summarise the similarities and differences between them. We would also like to emphasize the stylistical values of the translations.

Резюме. В Україні русини живуть у Карпатських горах уздовж кордонів Угорщини, Словаччини та Польщі. Русинські та українські балади можна згрупувати у чотири тематичні групи: історичні, розбійницькі, ліричні, родинно-побутові. Ласло Варі Фабіан, угорський поет, перекладач і фольклорист із Закарпаття, ознайомився з ру- синськими та українськими баладами Закарпаття будучи студентом університету, згодом переклав багато з них угорською мовою. Розпізнавання паралелей і відмінностей робить «трагедії, розказані в піснях», привабливими і для сучасних читачів. Текст з читачем об’єднує «герменевтична дуга». Робота присвячена культурному фону русинської та української народної балади, систематизації подібностей i відмінностей між ними. Указано на стилістичні цінності балад у перекладах.
Tragedies of Rusyn and Ukrainian Folkballads in the Hungarian Language
Трагедії русинського та українського фольклору угорською мовою
https://kmf.uz.ua/wp-content/uploads/2022/04/limes-2021-issue-viii_2021-12-30.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00009320
Keywords: folklór; népballada; ruszinok; ukránok; magyarok; fordítás; hermeneutika